Approximation of classes B^ω_p,θ of periodic functions of several variables by polynomials with spectrum from cubic areas (in Ukrainian) - S. A. Stasyuk (Математичні Студії, 2011)
We have obtained exact order estimates for error of approximation of classes B^ω_p,θ of periodic functions of several variables by trigonometric polynomials with spectrum from cubic areas.